Psychometric Assessment and Gender Invariance of the Polish Version of the Gaming Disorder Test. - Cudo, Andrzej; Montag, Christian; Pontes, Halley M. (International Journal of Mental Health & Addiction, 2024)
In 2019, Gaming Disorder (GD) was officially recognised by the World Health Organization (WHO) as an official mental health disorder. Currently, the Gaming Disorder Test (GDT) is one of the most widely utilised psychometric tools to assess GD symptoms according to the WHO framework. In this context, the present study aimed to develop the Polish version of the GDT so that this tool can be used within the Polish cultural context. Additionally, the research aimed to ascertain the psychometric properties and appropriateness of the Polish GDT. To achieve this goal, the Polish GDT was investigated in terms of its validity, reliability, and gender measurement invariance through two studies. Accordingly, study 1 recruited a total of 675 gamers (340 female; Mean = 31.74 years; SD = 7.75 years; range: 15–45 years) and study 2 comprised 575 gamers (275 female; M = 29.45 years; SD = 4.25 years; range: 18–35 years). A Confirmatory Factor Analysis (CFA) was used to assess psychometric properties of the Polish GDT. The reliability was assessed using Cronbach's alpha, McDonald's omega, and Average Variance Extracted. Gender measurement invariance was investigated using multiple-group CFA, and the unidimensionality was tested using mean of item residual absolute loadings (MIREAL), explained common variance (ECV), and unidimensional congruence (UC). The results of the psychometric analysis showed that the Polish GDT had a one-factor structure. Additionally, the present study demonstrated that the Polish GDT exhibited adequate levels of convergent validity, reliability, and strict gender measurement invariance. These findings suggest that the Polish version of GDT is a suitable psychometric test to assess GD and facilitate research on GD.